Peran Pemerintah dalam Mitigasi Resiko Abrasi di Nagari Pilubang Kabupaten Padang Pariaman - Oktarina, Winda; Alhadi, Zikri (Policy, Law and Political Research Center, 2024)
This study aims to examine the role of the government in abrasion risk mitigation efforts in Nagari Pilubang, Padang Pariaman Regency. This research uses a qualitative method with a descriptive approach, and the research location is in Korong Pasir Baru, Sungai Limau District, Nagari Pilubang, Padang Pariaman Regency. Informants were selected using a purposive sampling technique. Data were collected through observation, interviews, and documentation. The results showed that the role of the government in mitigating abrasion risk in Nagari Pilubang had yet to be optimally implemented. Based on Labolo's theory of the role of government, which includes the role of regulator, catalyst, and facilitator, this role has yet to be fully realized. This is due to several obstacles, such as a limited budget for mitigation, a lack of facilities and infrastructure, and low public awareness of disaster threats.